2021
DOI: 10.1002/ese3.1042
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hydrophilic and hydrophobic nano‐CaCO3 on kinetics of hydrate formation

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 52 publications
1
10
0
Order By: Relevance
“…Therefore, our findings indicate that calcite NPs will inhibit methane hydrate nucleation whenever the methane composition in solution is fixed by its solubility, as with water/gas two-phase systems. Our results thus give evidence for the experimental observations that hydrophilic NP inhibited hydrate nucleation because of its hydrophilicity, and if the weight percentage of nanoparticles in solution was fixed, the smaller the nanoparticle, the stronger the inhibition effect. , …”
Section: Resultssupporting
confidence: 77%
See 3 more Smart Citations
“…Therefore, our findings indicate that calcite NPs will inhibit methane hydrate nucleation whenever the methane composition in solution is fixed by its solubility, as with water/gas two-phase systems. Our results thus give evidence for the experimental observations that hydrophilic NP inhibited hydrate nucleation because of its hydrophilicity, and if the weight percentage of nanoparticles in solution was fixed, the smaller the nanoparticle, the stronger the inhibition effect. , …”
Section: Resultssupporting
confidence: 77%
“…It can explain the experimental conjecture that the agglomeration of nanoparticles can alter the surface wettability, thus influencing the inhibition effects. 25,26 We note that in the above system, when two NPs were inserted in the system, the mole fraction of methane molecules away from the NPs is increased due to an enhanced exclude-volume effect because the overall number of molecules was fixed. However, if a bulk gas phase is used in the configuration, the overall mole fraction of methane molecules in the solution is expected to be reduced (i.e., the methane composition in solution is fixed by its solubility).…”
Section: ■ Results and Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…They pointed out that the inhibition was related to the hydrophilicity. Similarly, Guo et al 54 concluded that although CaCO 3 nanoparticles promoted the formation of hydrate, the hydrophilic CaCO 3 nanoparticles aer modication inhibited the formation of hydrate. Xu et al 55 conducted wellbore simulation experiments and showed that the inhibition effect of the hydrophilic SiO 2 on hydrate in the wellbore increased with the increase in particle size.…”
Section: Effect In Drilling Fluid and Cement Slurrymentioning
confidence: 95%